LEGAL PROTECTION OF LABOR BASED ON POSITIVE LAW IN INDONESIA - Sarbini Sarbini (Warmadewa Press, 2024)
In an effort to increase legal protection for workes in Indonesia several sigificant laws and government regulations have been issued, such as Law no. 13 of 2003 concerning employment , the job creation law and government regulation no 51 of 2003 concerning wages. Legal protection in a country very necessary. Legal protection of labor is regulated in several laws in Indonesia , namely law no.13 of 2003 concerning employment, the job creation law, and government regulation no.51 of 2023 concerning wages. For employee eligibity, wage issues are also regulated using government regulation no 51 of 2021, wges are workers’ rights that are received as a from of compensation from employes which are paid according to an agreement or agreement between two parties, workes and entrepreneurs must also understand and carry out balanced right and obligations so that there is an efficient and dynamic work reltionship.